Run the Jewels 2 [compact disc]. (Mass Appeal, 2014)
El-P and Killer Mike, two of the most distinctive and celebrated names in rap, release their second album as a duo. The anticipated release also includes appearances from Travis Barker and Zack de la Rocha as well as the single Oh My Darling Don't Cry.